(1074) Social Development Planning. The Approach to Methodology at Macro and Micro Level تخطيط التنمية الاجتماعية : المنهجية الكلية والجزئية - Joseph Mihalik. (INP., 2020)
his paper approaches social development in a narrower sense, distinguishing it from the broader interpretation as the overall development of society. Here, "social" is primarily understood in relation to economic development, focusing on the efficient utilization of the human factor, the improvement of living standards, and the refinement of social structures. Social development, in this context, is closely linked to economic processes, yet it retains a degree of autonomy, exerting reciprocal influence on economic growth.Furthermore, emphasis is placed on greater public participation in management and administration, and on strengthening the unity between individuals and society. This interpretation shapes a specific approach to social development planning, one that regulates social processes rooted in economic realities, yet acknowledges their capacity to independently influence future development trajectories.